Legionella pneumophila in Thermal Spa – Methodological Aspects of Sampling and Analysis. Issue 5 (28th May 2019) - Mika, Anna; Kmiecik, Ewa; Krawiec, Arkadiusz; Wątor, Katarzyna; Zamfir, Mihai; Chochorek, Aneta
Abstract: The aim of the study was to check the occurrence of Legionella pneumophila in thermal water and to compare different analytical methods of its determination and/or quantification used in different laboratories. The research has shown that there are noticeable differences between results from culture method, qPCR, and FISH. Significant influence on the results has got analysts qualification, samples preparation, and equipment parameters. Very important is also the homogeneousness of the samples. qPCR or FISH method can be used as a preliminary, quick study, for identification of Legionella in water samples but the results obtained should be confirmed by culture method.